Situación actual de cáncer de piel en Ecuador - Neira Naranjo, Shirley Fernanda (2020)
Globally, skin cancer, mainly in continents like Europe and countries like the United States, has become a dangerous disease that today's society has had to face. At the Latin American level, numbers released by the World Health Organization (WHO) arouse the interest of experts and professionals who question how to combat this disease that is still growing.In Ecuador, a country that is crossed by the equator, sun's rays generate ultraviolet rays. These cause a high incidence rate of skin cancer in the country, by ultraviolet radiation. This is how this research proposes to show what the current situation of skin cancer in Ecuador is and what are the main factors for the incidence rate to increase. Within this journalistic investigation, the main types of carcinomas that affect Ecuadoreans are exposed. It also shows what their characteristics are. In addition, the investigation presents professionals’ and foundations’ opinions, as well as statistics to reach findings. Likewise, through four cases this investigation will show the way in which people who have lived with skin cancer live. However, within these stories, several differences were revealed and this is due to their social environment and economic situation, since two of the four cases were treated in public institutions and the other two people in private institutions. Finally, professionals and people suffering from skin cancer, make recommendations to citizens.